Silent voices : advancing your mindset for prosperity and inner peace - Gobardhan, Soeresh (Mahatt Institute Coral SpringsUS, 2003)
Leads one to a greater understanding of the benefits of an advanced mindset. Suggests ways of improving one's health, enhancing relationships, enriching spiritual growth, building new skills, setting new goals, and building more fulfilling lives.